Loyally, Luke : a novel [large type] - Basham, Pepper (THORNDIKE PRESS LARGE PRINT Christian Romance, 2024)
"Sometimes love means embracing the good, the bad . . . and even the impossible. Dear Reader, My name is Luke Edgewood, and there are few things in life that I require. Mainly black coffee. And flannel. And lots of solitude. And my dogs, Chewy and Indie. What I don't need is romance, so I have no plans to change my thirty-year-old bachelor status anytime soon. But my youngest sister thinks that by accepting a short-term construction job in the small European country of Skymar, I'm going to follow along in her footsteps and discover my own romantic adventure. Nope. Bah humbug. The End. This time, her rom-com-movie senses are totally wrong. Or maybe not. Because I've met a Grace Kelly look-alike who is annoying . . . until she isn't. But she is impossible. As in, nothing can happen between us because she is a literal princess. Even though that's easy to forget when we're working together to restore a castle-like orphanage in a secluded mountain town and "forced proximity" includes a small closet, a secret one-hundred-year-old journal, and the tactile memory of an off-limits royal in my arms. Basically, the whole situation has turned into an ooey gooey magical snow globe of romantic tropes complete with cute kids and an actual ball. Now, even my sentences are starting to sound like mush. Ugh. Send high levels of testosterone my way--I'm going to need it. Loyally, Luke"--